Macrofungal diversity of Hutan Simpan Sungai Menyala and Hutan Simpan Kenaboi, Negeri Sembilan - Jainuddin, Safawati (2019)
Macrofungal diversity is largely ignored in terms of biodiversity conservation of forests in Southeast Asia, especially for fragmented forests. Hence, this study is conducted to study the impact of microclimate, soil moisture, soil pH and canopy cover, on macrofungal diversity in fragmented forests. A total of 133 macrofungal morphospecies found in Hutan Simpan Sungai Menyala and Hutan Simpan Kenaboi. Six environmental parameters, soil moisture, temperature, soil pH, relative humidity, canopy cover and canopy closure were observed and recorded from all sites. Result showed that the most significant factors affecting macrofungal abundance are temperature, soil pH, soil moisture, canopy cover and type of substrate. Two significant factors affecting macrofungal morphospecies richness are type of substrate and relative humidity. These result showed that both HSSM and HSK had high biodiversity values of macrofungi. This study proved that macrofungal diversity is very important in conservation and preservation of biodiversity despite the fragmented forests.